Synthesis, structure and properties of N-alkoxy-N-(1-pyridinium) urea salts, N-alkoxy-N-acyloxyureas and N,N-dialkoxyureas - Shtamburg, Vasiliy; Штамбург, Василь Григорович; Shishkin, Oleg; Шишкін, Олег Васильович; Zubatyuk, Roman; Зубатюк, Роман Іванович; Kravchenko, Svetlana; Кравченко, Світлана Василівна; Tsygankov, Alexander; Циганков, Олександр Васильович; Shtamburg, Victor; Штамбург, Віктор Васильович; et al. (My University, 2007)
N-Alkoxy-N-(1-pyridinium)urea salts 3, 4 have been prepared, the conversions of N-acetoxy-N-methoxyurea 7 into N,N-dimethoxyurea 8 and of N-n-propyloxy-N-(1-pyridinium)-N',N'-dimethylurea chloride 6 into N,N-dimethoxy-N',N'-dimethylurea 11 were carried out. A high pyramidality of the amide nitrogen in O–N–X groups [X = N+C5H5, OMe, OC(O)C6H4Cl-p] has been revealed by XRD studies of ureas 3b, 8 and N-p-chlorobenzoyloxy-N-n-butyloxyurea 9. Отримано солі N-алкокси-N-(1-піридиній)сечовини 3, 4, перетворення N-ацетокси-N-метоксисечовини 7 в N,N-диметоксисечовину 8 та N-n-пропілокси-N-(1-піридинію) )-N',N'-диметилсечовини хлорид 6 в N,N-диметокси-N',N'-диметилсечовину 11. Висока пірамідальність амідного азоту в групах O–N–X [X = N+C5H5, OMe, OC(O)C6H4Cl-p] виявлена за допомогою XRD сечовини 3b, 8 та N-p-хлорбензоилокси-N-n-бутилоксисечовини 9.
Синтез, будова та властивості солей N -алкокси- N- (1-піридиній) сечовини, N -алкокси- N -ацилоксисечовини та N , N –діалкоксісечовини
Keywords: syntez; синтез; budova; будова; vlastyvosti solei; властивості солей